INDONESIAN AND ENGLISH EQUIVALENCE OF SLANG LANGUAGE IN “22 JUMP STREET” MOVIE - Nasrum Nasrum; Putri Oktavia Sari (UIN Alauddin Makassar, 2016)
AbstractThis thesis analyzed about “Indonesian and English Equivalence of Slang Language in “22 Jump Street Movie”. The aims of this research are to know the kinds of translation used in slang language, to know kinds of slang language itself used in the movie and to know the meaning equivalence between translated text and the original text in English slang language. This research used descriptive qualitative method and with three theories, they are Newmark’s, Partidge’s, and Palmer’s theories. The source of the data in this research was taken from the movie. The writers found two kinds of translations, they are semantic translation and communicative translation, while for the kinds of slang language the writer found jargon, argot, and colloquial. Therefore, the writer concluded that in 22 Jump Street movie the source language (SL) and the target language (TL) are not equivalent. AbstrakPersamaan Bahasa Prokem/Slang dalam Bahasa Indonesia dan Bahasa Inggris pada Film “22 Jump Street. Penelitian ini menganalisis persamaan bahasa prokem/slang dalam bahasa Indonesia dan bahasa Inggris pada “film 22 Jump Street”. Tujuan penelitian ini adalah untuk mengetahui jenis-jenis penerjemahan yang digunakan dalam bahasa prokem/slang, jenis bahasa prokem/slang itu sendiri dalam film tersebut dan mengetahui persamaan arti bahasa prokem/slang dalam Bahasa Sumber (BS) dan Bahasa Target (BT). Penelitian ini menggunakan metode deskriptif qualitative dengan tiga teori, antara lain: Teori dari Newmark, Partidge dan Palmer. Data diambil dari tuturan dalam film. Peneliti menemukan dua jenis penerjemahan yaitu penerjemahan semantik dan komunikatif. Di samping itu, jenis bahasa prokem/slang yang ditemukan adalah Jargon, Argot dan Colloquial. Kesimpulannya adalah Bahasa Sumber (BS) dan Bahasa Target (BT) dalam film 22 Jump Street tidak sama.